Migration and work-related mobility between the different metropolitan areas in the central region of Mexico - Granados-Alcantar, José Aurelio; Franco-Sánchez, Laura Myriam (Papeles de Población, 2017)
The importance of work-related mobility in metropolitan areas has gained significant attention. Therefore, this study sought to gain insight into the nature of work-related everyday travel in the Central Region of Mexico and as into the role these commutes play in the intra-metropolitan migration process currently taking place in the region. In order to accomplish these objectives, microdata from the 2010 Mexican population and housing census were employed to construct the relations between migration and work-related mobility in the nine metropolitan areas of Mexico's Central Region.